When Anxiety Erodes Intimacy: A Phenomenological Portrait of Marital Distress in Generation Z - Novia Sri Parindu Purba; Lidia Kastanya; Beatrice Brawijaya; Silvester Kalpika (Psikostudia : Jurnal Psikologi, 2026)
The phenomenon of delayed marriage among Generation Z indicates a value shift driven by deep-seated anxiety regarding potential marital distress. Economic factors do not merely trigger this hesitation but are deeply rooted in childhood experiences under authoritarian and neglectful parenting, which shape a traumatic perception of long-term commitment. Using a phenomenological approach, this study aims to explore how Generation Z individuals with such parenting backgrounds perceive their anxiety toward marriage. Thematic analysis was conducted on data from in-depth interviews with three Generation Z subjects (two females and one male). The findings confirm that marriage anxiety is a psychological construction stemming from primary relational experiences within the nuclear family. Neglectful and authoritarian parenting significantly distorts the subject's cognitive schemas, causing marriage to be perceived as a “high-risk relationship” that threatens affective stability. These dynamics are mapped into three major themes reflecting components of marital quality: dyadic consensus (alignment in values and life decisions), dyadic satisfaction (happiness in the relationship), and dyadic cohesion (emotional bond and togetherness). This study concludes that for Generation Z survivors of dysfunctional parenting, delaying marriage serves as a defense mechanism against the repetition of past trauma. Fenomena penundaan usia pernikahan pada Generasi Z mengindikasikan adanya pergeseran nilai yang didorong oleh kecemasan mendalam terhadap potensi marital distress. Keraguan ini tidak semata dipicu oleh faktor ekonomi, melainkan berakar kuat pada pengalaman masa kecil di bawah pola asuh authoritarian dan neglectful, yang membentuk persepsi traumatis terhadap komitmen jangka panjang. Dengan menggunakan pendekatan fenomenologi, penelitian ini bertujuan untuk mengekslporasi bagaimana Generasi Z dengan latar belakang pengasuhan tersebut mempersepsikan kecemasan mereka terhadap pernikahan. Analisis tematik dilakukan terhadap data wawancara mendalam dari tiga subjek Generasi Z (2 perempuan dan 1 laki-laki). Hasil temuan penelitian ini menegaskan bahwa kecemasan terhadap pernikahan merupakan konstruksi psikologis yang bersumber dari pengalaman relasional dalam keluarga inti. Pola asuh neglectful dan authoritarian mendistorsi skema kognitif subjek, sehingga pernikahan dipersepsikan sebagai relasi berisiko tinggi (high-risk relationship) yang mengancam stabilitas afektif. Dinamika ini terpetakan dalam tiga tema utama yang merefleksikan komponen kualitas pernikahan yaitu dyadic consensus (keselarasan dalam nilai dan Keputusan hidup), dyadic satisfaction (kepuasan dan kebahagiaan dalam hubungan), dan dyadic cohesion (ikatan emosional dan kebersamaan dalam hubungan). Penelitian ini menyimpulkan bahwa bagi Generasi Z penyintas pola asuh disfungsional, penundaan pernikahan adalah mekanisme pertahanan diri dari repetisi trauma di masa lalu.